Melatonin synthesis enzymes interact with ascorbate peroxidase to protect against oxidative stress in cassava. (31st May 2020) - Bai, Yujing; Guo, Jingru; Reiter, Russel J; Wei, Yunxie; Shi, Haitao
Abstract : Two enzymes of the melatonin synthesis pathway in cassava directly interact with ascorbate peroxidase (APX2) in vitro and in vivo, and the interaction promotes APX activity and antioxidant activity, resulting in improved oxidative stress resistance. Abstract: Melatonin is an important indole amine hormone in animals and plants. The enzymes that catalyse melatonin synthesis positively regulate plant stress responses through modulation of the accumulation of reactive oxygen species (ROS). However, the relationship between melatonin biosynthetic enzymes and ROS-scavenging enzymes has not been characterized. In this study, we demonstrate that two enzymes of the melatonin synthesis pathway in Manihot esculenta (MeTDC2 and MeASMT2) directly interact with ascorbate peroxidase (MeAPX2) in both in vitro and in vivo experiments. Notably, in the presence of MeTDC2 and MeASMT2, MeAPX2 showed significantly higher activity and antioxidant capacity than the purified MeAPX2 protein alone. These findings indicate that MeTDC2–MeAPX2 and MeASMT2–MeAPX2 interactions both activate APX activity and increase antioxidant capacity. In addition, the combination of MeTDC2, MeASMT2, and MeAPX2 conferred improved resistance to hydrogen peroxide in Escherichia coli . Moreover, this combination also positively regulates oxidative stress tolerance in cassava. Taken together, these findings not only reveal a direct interaction between MeTDC2, MeASMT2, and MeAPX2, but also highlight the importance of this interaction in regulating redox homoeostasis and stress tolerance in cassava.